Perancangan Optimasi Keamanan Operasional : Sistem Informasi Pengecekan Kondisi Gerbong Kereta Api Menggunakan Sistem Informasi Berbasis Web - Ali Ikhwan; Arya Dwi Utama; Suci Syah Putri; Deli Kartika Abrianisyah; Rizki Prasetya Nasution (Universitas Islam Raden Rahmat, Malang, 2024)
The operational safety of trains is a primary concern, where the physical condition of the carriages influences both safety and operational efficiency. This research proposes the development of a web-based system for checking the condition of train carriages to overcome the challenges of manual inspections. Descriptive methods were employed through observation, interviews, and documentary studies. The system adopts a digital approach to inspections, reducing the risk of errors and recording maintenance history. The results indicate that the implementation of this technology has significant potential to enhance the operational safety of railways significantly.